2016
DOI: 10.17795/jhealthscope-36776
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability of the Personnel of a Petrochemical Company and the Relationship Between Age and Physical Activities

Abstract: Background: Given the importance of the fit between workers' physical and mental abilities and their job needs, it is of great importance to assess, maintain and promote the work ability of the people. Objective: The current study, conducted in a petrochemicals company, aimed to assess the work ability of the personnel and its relationship with age and physical demands of work. Methods: The current cross sectional descriptive analytical study was conducted on 208 employees working in a petrochemical company. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Also, Tuomi et al [ 37 ] show that the probability of a low work ability increases with age. However, Abbashi et al [ 38 ], Wilke et al [ 39 ], and Golubic et al [ 40 ] state no significant impact of age on work ability. These results are in line with Padula et al [ 41 ], who found no differences between work ability in relation to age, but they observed an increase variability of responses for WAI score in older worker.…”
Section: Factors Influencing Work Motivation and Healthmentioning
confidence: 99%
“…Also, Tuomi et al [ 37 ] show that the probability of a low work ability increases with age. However, Abbashi et al [ 38 ], Wilke et al [ 39 ], and Golubic et al [ 40 ] state no significant impact of age on work ability. These results are in line with Padula et al [ 41 ], who found no differences between work ability in relation to age, but they observed an increase variability of responses for WAI score in older worker.…”
Section: Factors Influencing Work Motivation and Healthmentioning
confidence: 99%